CHROMITE-PLAGIOCLASE ASSEMBLAGES AS A NEW SHOCK INDICATOR; IMPLICATIONS FOR THE SHOCK AND THERMAL HISTORIES OF ORDINARY CHONDRITES - Rubin A.E. (My University, 2003)
Chromite in ordinary chondrites (OC) can be used as a shock indicator. A survey of 76 equilibrated H, L and LL chondrites shows that unshocked chromite grains occur in equant, subhedral and rounded morphologies surrounded by silicate or intergrown with metallic Fe-Ni and/or troilite. Some unmelted chromite grains are fractured or crushed during whole-rock brecciation. Others are transected by opaque veins; the veins form when impacts cause localized heating of metal-troilite intergrowths above the Fe-FeS eutectic (988°C), mobilization of metal-troilite melts, and penetration of the melt into fractures in chromite grains. Chromite-plagioclase assemblages occur in nearly every shock-stage S3-S6 OC; the assemblages range in size from 20-300 μm and consist of 0.2-20-μm-size euhedral, subhedral, anhedral and rounded chromite grains surrounded by plagioclase or glass of plagioclase composition. Plagioclase has a low impedance to shock compression. Heat from shock-melted plagioclase caused adjacent chromite grains to melt; chromite grains crystallized from this melt. Those chromite grains in the assemblages that are completely surrounded by plagioclase are generally richer in Al2O3 than unmelted, matrix chromite grains in the same meteorite. Chromite veinlets (typically 0.5-2 μm thick and 10-300 μm long) occur typically in the vicinity of chromite-plagioclase assemblages. The veinlets formed from chromite-plagioclase melts that were injected into fractures in neighboring silicate grains; chromite crystallized in the fractures and the residual plagioclase-rich melt continued to flow, eventually pooling to form plagioclase-rich melt pockets. Chromite-rich ''chondrules'' (consisting mainly of olivine, plagioclase-normative mesostasis, and 5-15 vol.% chromite) occur in many shocked OC and OC regolith breccias but they are absent from primitive type-3 OC. They may have formed by impact melting chromite, plagioclase and adjacent mafic silicates during higher-energy shock events. The melt was jetted from the impact site and formed droplets due to surface tension. Crystallization of these droplets may have commenced in flight, prior to landing on the parent-body surface.Chromite-plagioclase assemblages and chromite veinlets occur in 25 out of 25 shock-stage S1 OC of petrologic type 5 and 6 that I examined. Although these rocks contain unstrained olivine with sharp optical extinction, most possess other shock indicators such as extensive silicate darkening, numerous occurrences of metallic Cu, polycrystalline troilite, and opaque veins. It seems likely that these rocks were shocked to levels at least as high as shock-stage S3 and then annealed by heat generated during the shock event. During annealing, the olivine crystal lattices healed but other shock indicators survived. Published Ar-Ar age data for some S1 OC indicate that many shock and annealing events occurred very early in the history of the parent asteroids. The common occurrence of shocked and annealed OC is consistent with collisions being a major mechanism responsible for metamorphosing OC.